Pengaruh Dualitas CEO, Kualitas Audit Eksternal, dan Dewan Perempuan terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Kesehatan yang Terdaftar di Bursa Efek Indonesia Tahun 2019 - 2023 - Yunita, Vira; Nelvirita, Nelvirita (Universitas Negeri Padang, 2025)
This study aims to examine the effect of CEO duality, external audit quality and women on board on firm value. The variable used to measure firm value is Tobin's Q. The data used are secondary data in the form of annual reports of health sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample was determined using a purposive sampling technique and 16 companies were obtained as samples. This study uses a multiple linear regression analysis model. The results of this study indicate that CEO duality and external audit quality have a positive and significant effect on firm value. Meanwhile, women on board have a negative and significant effect on firm value.